Changes in Contribution of Causes of Death to Socioeconomic Mortality Inequalities in Korean Adults - Jung-Choi, Kyunghee (The Korean Society for Preventive Medicine, 2011)
OBJECTIVES: This study aimed to analyze long-term trends in the contribution of each cause of death to socioeconomic inequalities in all-cause mortality among Korean adults. METHODS: Data were collected from death certificates between 1990 and 2004 and from censuses in 1990, 1995, and 2000. Age-standardized death rates by gender were produced according to education as the socioeconomic position indicator, and the slope index of inequality was calculated to evaluate the contribution of each cause of death to socioeconomic inequalities in all-cause mortality. RESULTS: Among adults aged 25-44, accidental injuries with transport accidents, suicide, liver disease and cerebrovascular disease made relatively large contributions to socioeconomic inequalities in all-cause mortality, while, among adults aged 45-64, liver disease, cerebrovascular disease, transport accidents, liver cancer, and lung cancer did so. Ischemic heart disease, a very important contributor to socioeconomic mortality inequality in North America and Western Europe, showed a very low contribution (less than 3%) in both genders of Koreans. CONCLUSIONS: Considering the contributions of different causes of death to absolute mortality inequalities, establishing effective strategies to reduce socioeconomic inequalities in mortality is warranted.